KETEPATAN PEMERIKSAAN BTA APUSAN LANGSUNG DAN METODE KONSENTRASI DENGAN KULTUR DALAM MENDIAGNOSIS TUBERKULOSIS PARU DI MEDAN - Rahmah, Lestari; Tarigan, Amira Permatasari; M. Sinaga, Bintang Yinke (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2014)
Introduction: Tuberculosis diagnostic, using microscopic examination of direct smear of acid-fast bacili (AFB) from the spectrum of lung tuberculosis suspect is still important criteria today, but the sensitivity of this method is low enough, especially in the samples which contain a small number of bacteria. Culture is stronger, but it takes long time, high cost, and it is not conducted in all laboratories. BTA microscopic examination can use direct smear and concentration method. Staining technique which is usually used in microscopic examination is Ziehl Neelsen. The sensitivity of direct smear method tends to be low and can be increased by using concentration method because bacteria can be easily found. Objective of the research: The objective of the research was to find out the effectiveness of direct smear examination of AFB , and concentration method was compared with culture. Materials and Method: The samples consisted of 60 sputum samples from the patients of lung tuberculosis suspects who visited BP4 Medan and from private practices of tuberculosis specialists, and the samples had fulfilled inclusive criteria. Microscopic examination of acid-fast bacilli using direct smear and concentration method with Petroff method, using Ziehl Neelsen staining and culture with Lowenstein Jensen was conducted. Then we performed diagnostic test for direct smear and concentration method to compare it with culture. Result of the research: AFB examination with concentration method had sensitivity of 68.75%, specificity of 82.14%, the value of positive prediction of 81,48%, the value of negative prediction of 69.70%, ratio of positive likelihood of 3.85, and ratio of negative likelihood of 0.38, compared with culture method examination  in finding BTA in sputum of lung tuberculosis suspects. The result of microscopic examination of direct smear method had the sensitivity of 59.38%, specificity of 92.68%, the value of positive prediction of 90.48%, the value of negative prediction of 66.67%, ratio of positive likelihood of 8.31, and ratio of negative likelihood of 0.44, compared with culture method examination in finding BTA in sputum of lung tuberculosis suspects. Conclusion: The ability of acid-fast bacilli  examination of concentration methodsin diagnosis oflung tuberculosisis 9.37% higher thanthe directsmear but direct smear method gives bigger clinical benefit in diagnosing lung tuberculosis, compared with concentration method